DESAIN SISTEM KONTROL SUHU MENGGUNAKAN PID CASCADE DAN SAFETY PADA COLD STORAGE MENGGUNAKAN REFRIGERAN HIDROKARBON - Hariyanto, Arya Dwijaya; Rusli, Moch.; Yudaningtyas, Erni (Jurnal Mahasiswa TEUB, 2024)
Cold storage is a room for storing a product with a temperature that can be adjusted to suit the needs of the product. Properstorage is recommended to maintain product quality in the hands of consumers. The freshness of the product on delivery depends on temperature being less than 25oC. This study was conducted with the aim of observing the effect of storage temperature on the quality of products during shipment from the manufacturer to the hands of the consumer. Analysis of product storage on cold storage can maintain freshness and good quality of product. To condition the room temperature in the required batas, cold storage uses a steam compression refrigeration system to cool it down. Refrigeration can also be said to be a process of transferring heat from a material or room to another material or room (Ilyas, 1993). Hydrocarbon refrigerants are a sustainable solution as an environmentally friendly alternative, but have flammable properties. In order to overcome the risk of potential fire, advanced safety technologies such as PLC (Programmable Logic Controller) are required. The system is designed to be able to control temperature using the Ziegler-Nichols PID tuning method. To control it, a secondary controller (control valve) and a primary controller (temperature) are needed, where in this research the first Ziegler-Nichols method was used.The PLC programming method in this research is used for security purposes. The system is designed to be able to automaticallystop in cases of leaks. The test results show that the system can run according to the limits set with high pressure values of 161-249, low pressure 17-29, current <50, and voltage <380. Thus, PLC technology not only increases operational efficiency, but also ensures that the use of hydrocarbon refrigerants is carried out with the maximum level of safety. Keywords: refrigeran, cold storage, safety, temperature, cascade